2018
DOI: 10.29252/ijrm.16.6.365
|View full text |Cite
|
Sign up to set email alerts
|

Effects of antidepressants on parameters, melondiadehyde, and diphenyl-2-picryl-hydrazyl levels in mice spermatozoa

Abstract: Background:Prescribing antidepressant drugs is becoming common. These drugs are known to affect sexual functions.Objective:The study is aimed to assess the effects of amitriptyline and venlafaxine on sperm parameters and evaluate Malondialdehyde (MDA) and 1, 1-Diphenyl-2-picryl-hydrazyl values in BALB/ mice spermatozoa.Materials and Methods:Forty adult male BALB/c mice were separated into five groups. Group Ι (control) received distilled water; group ΙΙ amitriptyline (4 mg/kg); group ΙΙΙ amitriptyline (4 mg/kg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 35 publications
1
16
0
Order By: Relevance
“…Sperm motility was categorized as progressive, nonprogressive, and immotile spermatozoa. The percentage of sperm cells with normal morphology in the head, neck/mid-piece, and tail were obtained by Diff-Quik staining using light microscopy (×1,000 magnification) ( Figure 1A ) [ 18 ].…”
Section: Methodsmentioning
confidence: 99%
“…Sperm motility was categorized as progressive, nonprogressive, and immotile spermatozoa. The percentage of sperm cells with normal morphology in the head, neck/mid-piece, and tail were obtained by Diff-Quik staining using light microscopy (×1,000 magnification) ( Figure 1A ) [ 18 ].…”
Section: Methodsmentioning
confidence: 99%
“… 11 Different studies indicate that the antidepressants could have negative influence on the male reproductive system. 8 …”
Section: Introductionmentioning
confidence: 99%
“…The only prior published study that we can identify examining SNRI effects on male fertility potential was performed in mice. In this study, mice received venlafaxine with or without vitamin C and were compared with controls (Bandegi et al., 2018). Mice treated with SNRI had better sperm morphology, nonprogressive motility and viability, but no difference in sperm concentration (Bandegi et al., 2018).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, mice received venlafaxine with or without vitamin C and were compared with controls (Bandegi et al., 2018). Mice treated with SNRI had better sperm morphology, nonprogressive motility and viability, but no difference in sperm concentration (Bandegi et al., 2018). Interestingly, the authors reported these differences in contrast to studies with SSRIs, citing that differences in medication effect may have been due to drug dosage and the animal model itself (Bandegi et al., 2018).…”
Section: Discussionmentioning
confidence: 99%